Hydrography and energetics of a cold subpolar fjord: Andvord Bay, western Antarctic Peninsula. (February 2020) - Lundesgaard, Øyvind; Winsor, Peter; Truffer, Martin; Merrifield, Mark; Powell, Brian; Statscewich, Hank; Eidam, Emily; Smith, Craig R.
Abstract: Fjords along the western Antarctic Peninsula contain rich marine ecosystems and tidewater glaciers potentially sensitive to ocean change, but much is unknown about the physical oceanography of these fjords. This paper presents a comprehensive description of the physical environment of Andvord Bay, a glacial fjord located in the Gerlache Strait on the northern end of the Peninsula. Measurements were collected as part of the FjordEco program between November 2015 and March 2017, including during three research cruises and from a number of fixed installations (sub-surface moorings, time lapse cameras, and automatic weather stations). Andvord Bay is located just north of a sill in the Gerlache Strait. This sill inhibits the direct influence of warm Upper Circumpolar Deep Water from the shelf, and deep waters in the fjord are therefore relatively cold. As a result, glaciers in Andvord Bay are not subject to the substantial ocean-driven retreat observed farther south on the Peninsula. Instead, mass flux from the glaciers occurs mainly through calving. The influence of meltwater in Andvord Bay is small compared to glacial fjords in the Arctic and in the South Shetland Islands, although summer freshening is evident in the fjord near-surface layer, likely as a result of glacial inputs. The combination of surface freshening and the absence of strong mean wind forcing in the fjord results in salinity stratification extending well into the euphotic zone, providing advantageous conditions for phytoplankton blooms. Andvord Bay is generally dynamically quiet compared to the ambient ocean, with the exception of during local katabatic wind events. Exchange with the Gerlache Strait is weak, although the deep waters of the fjord are replenished on an annual scale through slow lateral exchange with the outside. In addition, deep convection may play a role in ventilating subsurface waters in winter.